Från omhändertagande till ansvarstagande: Nyliberal hälsa i etableringen av nyanlända - Silow Kallenberg, Kim; Sigvardsdotter, Erika (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2018)
This article analyses documents related to the civic orientation courses for newly arrived refugees in Sweden, using a discourse theoretical logics approach. The aim is to explore the ideas that characterise the course material, especially in relation to health. The analytical focus of the article is health related discourses and how they are motivated in the course material. The analysis identifies a social logic of individual responsibility, where the subject is expected to actively improve their health through exercise and a healthy diet. The fantasmatic aspects of this logic conceal the fact that our health to ha high extent is affected by structural factors, and produces a fantasy of individuals being able to “choose their health”. These logics are part of the wider neoliberal shift in Swedish political discourse. We interpret the focus on neoliberal health practices as something constitutive of what it means to be Swedish in today’s context. An overarching aim of civic orientation courses is to teach newly arrived refugees about Swedish norms and values. By articulation of these norms, Swedishness is produced and reproduced.